High-Throughput Genotyping with Single Nucleotide Polymorphisms - Ranade, Koustubh (Cold Spring Harbor Laboratory Press, 2001)
To make large-scale association studies a reality, automated high-throughput methods for genotyping with single-nucleotide polymorphisms (SNPs) are needed. We describe PCR conditions that permit the use of the TaqMan or 5′ nuclease allelic discrimination assay for typing large numbers of individuals with any SNP and computational methods that allow genotypes to be assigned automatically. To demonstrate the utility of these methods, we typed >1600 individuals for a G-to-T transversion that results in a glutamate-to-aspartate substitution at position 298 in the endothelial nitric oxide synthase gene, and a G/C polymorphism (newly identified in our laboratory) in intron 8 of the 11–β hydroxylase gene. The genotyping method is accurate—we estimate an error rate of fewer than 1 in 2000 genotypes, rapid—with five 96-well PCR machines, one fluorescent reader, and no automated pipetting, over one thousand genotypes can be generated by one person in one day, and flexible—a new SNP can be tested for association in less than one week. Indeed, large-scale genotyping has been accomplished for 23 other SNPs in 13 different genes using this method. In addition, we identified three “pseudo-SNPs” (WIAF1161, WIAF2566, and WIAF335) that are probably a result of duplication.